Inadequacy of a model of discipleship in respect of the decline of youth ministry in Rustenburg/Tlhabane Uniting Reformed Church in South Africa (URCSA) - Vellem, Vuyani Shadrack (University of Pretoria, 2017)
Dissertation (MA (Theology))--University of Pretoria, 2016.